Pembentukan Tanaman Cabai Haploid Melalui Induksi Ginogenesis dengan Menggunakan Serbuk Sari yang Diradiasi Sinar Gamma - Suharsono, ,; Alwi, Muhammad; Purwito, Agus (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The objective of this research was to obtain haploid hot pepper plants by inducing gynogenesis with g-ray irradiated pollen for pollination. Fruits resulted from pollination by irradiated pollen was used as the explants of the in vitro culture in solid MS medium containing BAP, IAA and GA3. The resulted plants then cultivated in MS0 medium. The result of the research showed that hot pepper immature embryo could grow and developed into whole plant when the age of this embryo was 9 days after pollination or more. The haploid hot pepper plants can be obtained by pollinating the pistil with 10 Gy irradiated pollen. The MS medium containing BAP 0.3 + IAA 0.2 + GA3 0.5 mg/l and BAP 0.4 + IAA 0.1 + GA3 0.5 mg/l supported well the development of immature embryo into whole plants. The growth of haploid hot pepper plants was slower than that of diploid ones. Key words: Hot pepper, haploid plant, gynogenesis, g-ray.